2018
DOI: 10.1016/j.clinimag.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features of malignant abdominal neuroendocrine tumors with rare presentation

Abstract: The diagnosis of NETs is challenging and generally based on clinical manifestations, blood biochemical tests, imaging techniques, and pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Since all tumors in each MEN1-/MEN2-groups exhibit similar imaging characteristics and all histopathologically proven LM confirmed a NET pattern, we believe that this does not taper our results. Moreover, it has been previously shown that the imaging features of NET in a contrast-enhanced CT correlate the histological findings [34, 35]. Another limitation in our study was the variable modalities in the follow-up-controls.…”
Section: Discussionmentioning
confidence: 83%
“…Since all tumors in each MEN1-/MEN2-groups exhibit similar imaging characteristics and all histopathologically proven LM confirmed a NET pattern, we believe that this does not taper our results. Moreover, it has been previously shown that the imaging features of NET in a contrast-enhanced CT correlate the histological findings [34, 35]. Another limitation in our study was the variable modalities in the follow-up-controls.…”
Section: Discussionmentioning
confidence: 83%
“…The 18F-FDOPA PET tracer provides additional metabolic and functional information that gives valuable additional diagnostic data on patients with NETs [16]. Corrias et al reported imaging features of malignant abdominal neuroendocrine tumors with rare presentation in four patients [27]. The location and type of NENs could influence the sensitivity of the diagnostic methods.…”
Section: Discussionmentioning
confidence: 99%